Examining student engagement in online ideological and political learning within vocational colleges in China - Sun, Chunxiu; Abdulrazak Yahya, Saleh (UNIMAS Publisher, 2025)
This study examines student engagement in online ideological and political (I&P) courses at higher vocational institutions during the pandemic's shift to online education. Recognising limited research on engagement in such politically charged remote learning contexts, the study investigates institutional, technological, and pedagogical drivers (RQ1) and grade-level variations in interaction patterns (RQ2). Integrating Activity Theory, Social Interaction, and Critical Pedagogy frameworks, a 12-dimensional questionnaire was developed, validated, and applied to 611 responses. This research fills a critical gap by examining engagement where ideological discourse intersects with remote learning constraints, proposing an integrated AT-SOI-CP framework to reconcile technical and sociopolitical dimensions of online I&P education. Quantitative analysis found student-teacher, student-student, and tool use significantly predicted content engagement. However, statistical analysis showed no significant differences in student-teacher interaction (H = 5.178, df = 3, p = 0.159), student-student interaction (H = 7.309, df = 3, p = 0.063), or student-content interaction (H = 5.661, df = 3, p = 0.129) across academic years. The study concludes with recommendations for optimising online pedagogies in I&P courses, emphasising structured collaboration and equitable power dynamics. These findings contribute theoretically and practically to understanding how technological, social, and pedagogical factors shape engagement in evolving educational landscapes.